Excel 2010 for educational and psychological statistics : a guide to solving practical problems - Quirk, Thomas (Springer New York, 2012)
This is the first book to show the capabilities of Microsoft Excel to teach educational and psychological statistics effectively.  It is a step-by-step exercise-driven guide for students and practitioners who need to master Excel to solve practical problems in education and psychology.  If understanding statistics isn't your strongest suit, you are not especially mathematically-inclined, or if you are wary of computers, this is the right book for you.    Excel, a widely available computer program for students and practitioners, is also an effective teaching and learning tool for quantitative analyses in statistics courses.  Its powerful computational ability and graphical functions make learning statistics much easier than in years past.  However, Excel 2010 for Educational and Psychological Statistics: A Guide to Solving Practical Problems is the first book to capitalize on these improvements by teaching students and practitioners how to apply Excel to statistical techniques necessary in their courses and work.   Each chapter explains statistical formulas and directs the reader to use Excel commands to solve specific, easy-to-understand problems in education and psychology.  Practice problems are provided at the end of each chapter with their solutions in an appendix.  Separately, there is a full Practice Test (with answers in an Appendix) that allows readers to test what they have learned.   Includes 163 illustrations in color.